Perspectives of Long Non-Coding RNAs in Cancer Diagnostics - Reis, Eduardo M.; Verjovski-Almeida, Sergio (Frontiers in Genetics, 2012)
Long non-coding RNAs (lncRNAs) transcribed from intergenic and intronic regions of the human genome constitute a broad class of cellular transcripts that are under intensive investigation. While only a handful of lncRNAs have been characterized, their involvement in fundamental cellular processes that control gene expression highlights a central role in cell homeostasis. Not surprisingly, aberrant expression of regulatory lncRNAs has been increasingly documented in different types of cancer, where they can mediate both oncogenic or tumor suppressor effects. Interaction with chromatin remodeling complexes that promote silencing of specific genes or modulation of splicing factor proteins seem to be two general modes of lncRNA regulation, but it is conceivable that additional mechanisms of action are yet to be unveiled. LncRNAs show greater tissue specificity compared to protein-coding mRNAs making them attractive in the search of novel diagnostics/prognostics cancer biomarkers in body fluid samples. In fact, lncRNA prostate cancer antigen 3 can be detected in urine samples and has been shown to improve diagnosis of prostate cancer. We suggest that an unbiased screening of the presence of RNAs in easily accessible body fluids such as serum and urine might reveal novel circulating lncRNAs as potential biomarkers in many types of cancer. Annotation and functional characterization of the lncRNA complement of the cancer transcriptome will conceivably provide new venues for early diagnosis and treatment of the disease.